Evolutionary stability of plant–pollinator networks: efficient communities and a pollination dilemma - Metelmann, Soeren; Sakai, Shoko; Kondoh, Michio; Telschow, Arndt; Brose, Ulrich (Ecology letters, 2020)
Mutualistic interactions between species are ubiquitous in nature and essential for ecosystem functioning. Often dozens or even hundreds of species with different degrees of specialisation form complex networks. How this complexity evolves is a fundamental question in ecology. Here, we present a new game theoretical approach to model complex coevolutionary processes and apply it to pollination networks. A theoretical analysis reveals multiple evolutionary stable network structures that depend on the availability of pollination service. In particular, we find efficient communities, in which a high percentage of pollen are transported conspecifically, to evolve only when plant and pollinator abundances are well balanced. Both pollinator shortage and oversupply select for more inefficient network structures. The results suggest that availability of pollination services is a key factor structuring pollination networks and may offer a new explanation for geographical differences in pollination communities that have long been recognised by ecologists. In plant‐pollinator interactions, often dozens or even hundreds of species with different degrees of specialization form complex networks. Here, we present a new game theoretical approach to understand the coevolutionary processes in these networks. The results suggest that availability of pollination services is a key factor structuring pollination networks and may offer a new explanation for geographical differences in pollination communities.